Measurement of Indoor-Outdoor Carbonyls in Three Different Universities Located in the Metropolitan Zone of Mexico Valley during the First Period of Confinements Due to COVID-19 - Rocío García; Sandra Silva Gómez; Gema Andraca; Ricardo Torres Jardón; Agustín García Reynoso; Julia Griselda Cerón; Rosa María Cerón; Violeta Mugica Alvarez (Atmosphere, 2022)
Carbonyl concentrations in indoor-outdoor air were measured at three urban sites in the Metropolitan Zone of Mexico Valley (MZMV) during the first period of confinements due to COVID-19; the exposure for people living in indoor environments was also assessed. Indoor and outdoor samples were simultaneously collected sequentially with Sep-Pack DNPH-Silica cartridges. Formaldehyde, acetaldehyde, acetone, propionaldehyde, butyraldehyde and acrolein were quantified according to the US-EPA TO-11A method. Acrolein and acetone were the most abundant carbonyls in indoor air, with average concentrations of 55.5 µg m−3 and 46.4 µg m−3, respectively, followed by formaldehyde (29.1 µg m−3), acetaldehyde (21.4 µg m−3) and butyraldehyde (7.31 µg m−3). Propionaldehyde was not detected. Acetone was the dominant carbonyl in outdoor samples with an average concentration of 8.4 µg m−3, followed by formaldehyde (2.8 µg m−3) and acetaldehyde (0.7 µg m−3). Butyraldehyde and acrolein were not detected in outdoor air. Indoor/outdoor (I/O) ratios showed that indoor sources prevail for most aldehydes. Statistical analysis of simple correlations showed that the measured carbonyls were influenced by the presence of indoor sources. The average cancer risk coefficients (LTCR) for formaldehyde and acetaldehyde and the non-cancer risk coefficients (HQ) for acrolein and formaldehyde were higher than the recommended limits, which should be a cause for public concern.